MEMORY OF A DISASTER: THE 1951 FLOOD IN CERVANTES DE ALVARADO - Granados Jiménez, Rodrigo (2025)
The impact of extreme natural events can be signicant on society, the economy and the environment and become part of the collective memory, especially if they have involved the loss of human life. Due to their greater scope of impact, natural events of geophysical origin, earthquakes and volcanic eruptions have been historiographically the most studied in Costa Rica, while events of hydrological origin that involve the death of people, such as landslides or large heads of water, have been little studied, not remembered or forgotten. This essay addresses a disaster that occurred in 1951 in Costa Rica in the district of Cervantes, canton of Alvarado, province of Cartago, which caused the death of more than a dozen people, to study the causes of why some natural disasters risk being forgotten. Recovering the historical memory of these events enriches the understanding of the collective society-environment dynamic in the community where the events occurred and the sites of occurrence can become natural museums that remember the evidence of the event as legitimate places of memory for the inhabitants of a community.